The Introduction of the Informatics Potential and the Kinetics of Informatics: The Spontaneous and Non-Spontaneous Enmorphy (Global Journal of Science Frontier Research, 2019)
In this paper the Informatics Potential is introduced as a consequence of the four energetic potentials, namely, dH the enthalpy, dA the free energy of Helmholtz, dG the free energy of Gibbs and dE the internal energy, and the chemical potential dμ ι . In the informatics, the matter is the Information and the Enmorphy, and for this reason, the Informatics Potential was introduced. Then, a general and unified kinetic theory of informatics was presented, similar to chemical kinetic theory. The main issue is the transformation of Information into Order. The order, in this case, means: structure, organization, form, aligning, composition, establishment, grouping, layout, pattern, scale, sequence, symmetry and uniformity and all other notions which can be understood as the order. The general kinetic theory of informatics can be applied to all areas of science, i.e, physics, chemistry,